(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
Moral and ethical education in primary schooling faces renewed urgency amid digital media saturation, social polarization, and growing attention to children’s wellbeing. While traditional character education and moral reasoning approaches remain influential, contemporary classrooms increasingly require innovative, evidence-informed methods that engage learners cognitively, emotionally, socially, and culturally. This article reports a design-oriented integrative study that synthesizes research on (a) moral development and character education, (b) social-emotional learning (SEL), and (c) technology-enhanced pedagogy to propose an innovation framework for moral and ethical education in Grades 1–4. Using a structured scoping review and thematic synthesis, we identify five high-leverage instructional innovations-digital storytelling, gamification, project-based learning, interactive technologies, and culturally responsive pedagogy-aligned with global policy priorities and competency frameworks (UNESCO, UNICEF, OECD). Results include a multi-layer “VALUES” model (Virtues, Agency, Life-world relevance, Understanding/Reasoning, Engagement, Social responsibility) and a practical implementation architecture linking universal classroom practices with targeted supports. The discussion examines how innovations can avoid common pitfalls (moralizing, superficial “points and badges,” cultural essentialism, or surveillance-like edtech), and proposes ethically grounded evaluation indicators that measure moral sensitivity, reasoning, identity, and prosocial action. Recommendations highlight teacher professional learning, family–community partnership, and culturally responsive design as conditions for sustainable impact.